1960
DOI: 10.1111/j.1550-7408.1960.tb00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscope Study of the Exoerythrocytic Form of Plasmodium gallinaceum in Thin Sections of Infected Tissue Cultures*

Abstract: SYNOPSIS. The exoerythrocytic forms of Plasmodium gallinaceum in thin sections of infected tissue cultures have been examined with the electron microscope. It was seen that important changes occur in the fine structure of the parasite during the various phases of the cycle. The cytoplasm of the merozoites at the beginning and at the end of each cycle shows a great electron density due to a fine granulation. Larger granules are found at one pole of the parasite. The merozoites have a large nucleus in the center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1962
1962
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 11 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…The presence of multinucleated cells, containing several, preformed organanisms in a rosette arrangement, corresponds to a type of propagation usually designated as schizogony. Furthermore, electron microscope observations on the segmenter phase in the schizogonic cycle of other protozoa, Plasmodium gallinaceum (13) and Plasmodium lophurae ( 16), closely accord with those obtained from the Toxoplasma rosettes. The residual cytoplasmic material connected by strands with the filial organisms appears to correspond to the residual body observed in the malarial parasites.…”
Section: Discussionsupporting
confidence: 80%
“…The presence of multinucleated cells, containing several, preformed organanisms in a rosette arrangement, corresponds to a type of propagation usually designated as schizogony. Furthermore, electron microscope observations on the segmenter phase in the schizogonic cycle of other protozoa, Plasmodium gallinaceum (13) and Plasmodium lophurae ( 16), closely accord with those obtained from the Toxoplasma rosettes. The residual cytoplasmic material connected by strands with the filial organisms appears to correspond to the residual body observed in the malarial parasites.…”
Section: Discussionsupporting
confidence: 80%
“…I t is encased in a double membrane (Figs. 1-3, 7-9, [16][17][18]21). To the outer membrane ribonucleoprotein particles are attached.…”
Section: Resultsmentioning
confidence: 99%
“…Droplets of host cytoplasm are trapped into these invaginations with the subsequent formation of food vacuoles. This assumption is strengthened by two facts: 1) Malaria parasites in their exoerythrocytic stage, and therefore in a different type of host cell, have not been observed to feed by pinocytosis (21); 2) However, Babesia, an unrelated parasite which also lives intracellularly in erythrocytes, feeds on the host cell in exactly the same way as malarial parasites in their intraerythrocytic stage (38). Both facts indicate that there is a close relationship between the surrounding medium and the manner of feeding in these parasites.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro cultures of EEF of avian malaria have been successfully obtained with tissue explants from birds or embryos previously infected with sporozoites or blood parasites [5,6,8,10,15,16,19,201. However, Dubin et al [l], reported negative results by several groups in their attempts to obtain EEF directly from sporozoites in vitro.…”
mentioning
confidence: 99%